1998
DOI: 10.1021/jm970327j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticonvulsant Activity, and Structure−Activity Relationships of Sodium Channel Blocking 3-Aminopyrroles

Abstract: Starting from the corresponding acetophenone and glycine derivatives, a series of new 3-aminopyrroles was synthesized in few steps. Using this procedure with hydrazine and hydroxylamine instead of the glycinates provides access to 3-aminopyrazoles and 5-amino 1,2-oxazoles. The various derivatives were tested for anticonvulsant activity in a variety of test models. Several compounds exhibit considerable activity with a remarkable lack of neurotoxicity. 4-(4-Bromophenyl)-3-morpholinopyrrole-2-carboxylic acid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(73 citation statements)
references
References 48 publications
3
69
0
1
Order By: Relevance
“…Methyl (or alkyl) substitutions of the amide nitrogens of the hydantoin ring reduced binding significantly (Brown et al, 1997), which underlines the importance of these hydrogens for binding. It has been proposed that one aromatic ring and one amide group of the hydantoin form the pharmacophore core of phenytoin (Unverferth et al, 1998;Brown et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Methyl (or alkyl) substitutions of the amide nitrogens of the hydantoin ring reduced binding significantly (Brown et al, 1997), which underlines the importance of these hydrogens for binding. It has been proposed that one aromatic ring and one amide group of the hydantoin form the pharmacophore core of phenytoin (Unverferth et al, 1998;Brown et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…This requirement was further evidenced by compounds 4k-4y and 5k-5y where the -OH function was replaced by a -Cl, CH 3 or -NO 2 moiety. The complete loss of activity due to the disappearance of this function could be explained in terms of interaction at the binding site by the pharmacophoric models which were previously proposed [30][31][32][33] (Scheme 2). In these models, it has been reported that the existence of a hydrophobic unit (Ar), an electron donor group (D) and hydrogen-bonding domain (HBD) was essential for anticonvulsant activity, as evidenced by the active drugs, such as carbamazepine or phenytoin, fulfilling these demands.…”
Section: Methodsmentioning
confidence: 99%
“…Several pyrazole derivatives have been reported possessing important pharmacological activities which now are useful materials in drug research. In 1998, Unverferth et al 15 described a series of 3-aminopyrroles as anticonvulsants, in which an interaction between pyrrole and voltage-dependent sodium channel were established. As a backup, 3-amino-and 5-aminopyrazoles were also prepared.…”
Section: -14mentioning
confidence: 99%